Esophageal duplication cyst in an adult masquerading as hydatid cyst - Palle, Pranay; Mulpuri, Venu Bhargav; Ramavath, Krishna; Lavudya, Gopisingh; Kallem, Srinivas Reddy (International Surgery Journal, 2022)
Esophageal duplication cysts are congenital anomalies of the foregut, occurring due to aberration of the posterior division of the embryonic foregut at 3-4 wk gestation. These inherited lesions usually diagnosed in early childhood and rare in adult age group. We are reporting this case as esophageal duplication cyst in an adult female patient which is masquerading as hydatid cyst of liver. We are reporting one case of esophageal duplication cyst in a adult patient which is a rare condition to occur in this age group and managed successfully by laparoscopic approach. Esophageal duplication cyst, though it is a rare condition, should keep in mind ason of the differential diagnosis for the cystic lesions arising from gastroesopahegal junction. It can be managed by laparoscopic approach.